2019
DOI: 10.3390/jcdd6020017
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Adherence of Saudi Males to the Saudi Dietary Guidelines and Its Relation to Cardiovascular Diseases: A Preliminary Cross-Sectional Study

Abstract: Cardiovascular disease (CVD) is a major public health problem in Saudi Arabia. Dietary intake plays a major role in CVD incidence; however, the dietary intake status in Saudi nationals with CVD is unknown. We aimed to investigate whether the dietary patterns of Saudi males, using the Saudi dietary guidelines adherence score, in parallel with the measurement of a selective number of cardiovascular disease-related biomarkers, are contributing factors to CVD risk. Demographics, dietary adherence score, and blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 36 publications
0
25
1
Order By: Relevance
“…( Moradi-Lakeh et al, 2017 ) Another interesting study indicated that the high consumption of olive oils among male Saudis seems to help lower the rate of cardiovascular disease. ( Alkhaldy et al, 2019 ) Unfortunately, the risk factor management or lifestyle changes is poor in Saudi Arabia as confirmed by the study conducted by Robert et al (2018) where only 23% of hypertensive patients were even aware that they have elevated blood pressures which co-exist with undiagnosed diabetes with micro- (28%) and macro-vascular complications (50%). ( Robert et al, 2018 )…”
Section: Prevalence and Incidencementioning
confidence: 99%
“…( Moradi-Lakeh et al, 2017 ) Another interesting study indicated that the high consumption of olive oils among male Saudis seems to help lower the rate of cardiovascular disease. ( Alkhaldy et al, 2019 ) Unfortunately, the risk factor management or lifestyle changes is poor in Saudi Arabia as confirmed by the study conducted by Robert et al (2018) where only 23% of hypertensive patients were even aware that they have elevated blood pressures which co-exist with undiagnosed diabetes with micro- (28%) and macro-vascular complications (50%). ( Robert et al, 2018 )…”
Section: Prevalence and Incidencementioning
confidence: 99%
“…Several studies have been conducted to investigate dietary quality among adults in the KSA (Al-Shoshan, 2007; Moradi-Lakeh et al, 2017; Thorpe et al, 2014). Most of these studies have assessed diet quality based on either a diet history questionnaire that did not contain details of all types of foods and beverages (Al-Shoshan, 2007; Mandoura et al, 2017; Moradi-Lakeh et al, 2017) or Saudi dietary guidelines (Alkhaldy et al, 2019; Saudi Ministry of Health, 2012). Moreover, one study used the dietary guideline index (DGI), which was designed to assess adherence to Australian dietary guidelines (Thorpe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…NAB consumption is thought to have positive action on a cardiovascular level as a cross-sectional study has shown that healthy people drink more of it than people suffering from cardiovascular disease. Moreover, people free of CVD have more fruits and olive oil in their daily meals [126].…”
Section: Positive Action At Cardiovascular Levelmentioning
confidence: 99%